2008
DOI: 10.1111/j.1744-7909.2008.00759.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Signaling in Plant Responses to Abiotic Stresses

Abstract: Nitric oxide (NO) plays important roles in diverse physiological processes in plants. NO can provoke both beneficial and harmful effects, which depend on the concentration and location of NO in plant cells. This review is focused on NO synthesis and the functions of NO in plant responses to abiotic environmental stresses. Abiotic stresses mostly induce NO production in plants. NO alleviates the harmfulness of reactive oxygen species, and reacts with other target molecules, and regulates the expression of stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
102
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(113 citation statements)
references
References 107 publications
(151 reference statements)
6
102
0
5
Order By: Relevance
“…2 E and F; P < 0.05). The opposite effect of NO on the activities of SNO1 and PDX3 we observed could be a competitive result between these two salvage pathway enzymes facing NO treatment, and the increase of SNO1 activity in response to SNP treatment may suggest a prominent role of SNO1 enzyme in stress responses because NO is a well-known stress-induced signaling molecule (43,44). Consistent with this concept, previous study showed that the expression of SOS4 (or SNO1) is regulated by several environmental stimuli (36).…”
Section: Resultsmentioning
confidence: 87%
“…2 E and F; P < 0.05). The opposite effect of NO on the activities of SNO1 and PDX3 we observed could be a competitive result between these two salvage pathway enzymes facing NO treatment, and the increase of SNO1 activity in response to SNP treatment may suggest a prominent role of SNO1 enzyme in stress responses because NO is a well-known stress-induced signaling molecule (43,44). Consistent with this concept, previous study showed that the expression of SOS4 (or SNO1) is regulated by several environmental stimuli (36).…”
Section: Resultsmentioning
confidence: 87%
“…Recently, the role of NO in the regulation of stomatal closure has been well documented, and a growing body of literature shows that the potential enzymatic sources of NO in guard cells are nitric oxide synthase (NOS) and NR (Neill et al, 2002Qiao and Fan, 2008). However, so far, no genes or proteins with sequence homology to known mammalian-type NOS have been found in plants (Guo et al, 2003;Crawford, 2006).…”
Section: Nia1-dependent No Mediates Uv-b-induced Stomatal Closurementioning
confidence: 99%
“…Recently, compelling evidence emerged that hydrogen peroxide (H 2 O 2 ) and nitric oxide (NO) function as signaling molecules in plants, mediating a range of responses to environmental stress including UV-B radiation (Neill et al, 2002;Qiao and Fan, 2008;Wilson et al, 2008). Increasing evidence also points to the role for H 2 O 2 and NO as essential components in guard cell signaling.…”
mentioning
confidence: 99%
“…Nitric oxide controls a signaling cascade that regulates plant responses to developmental processes, biotic and abiotic stress 48, 49, 50, 51. We have found induced expression in the AdZADH2 transcripts at late stage of SNP treatment.…”
Section: Resultsmentioning
confidence: 63%